A Selective C−H Deprotonation Strategy to Access Functionalized Arynes by Using Hypervalent Iodine. (30th May 2016) - Sundalam, Sunil K.; Nilova, Aleksandra; Seidl, Thomas L.; Stuart, David R.
Abstract: Described here is an efficient method to access highly functionalized arynes from unsymmetrical aryl(mesityl)iodonium tosylate salts. The iodonium salts are prepared in a single pot from either commercially available aryl iodides or arylboronic acids. The aryne intermediates are generated by ortho ‐C−H deprotonation of aryl(mesityl)iodonium salt with a commercially available amide base and trapped in a cycloaddition reaction with furan in moderate to good yields. Coupling partners for the aryne intermediates beyond furan are also described, including benzyl azide and alicyclic amine nucleophiles. The regio‐ and chemoselectivity of this reaction is discussed and evidence for the spectator aryl ligand of the iodonium salt as a critical control element in selectivity is presented.